Flavonoids A Coloring Model for Cheering up Life - Badria, Farid A.; Ananga, Anthony (Biochemistry, 2020)
Flavonoids with over 6000 natural colorful compounds are a unique class of phytonutrients found in almost all vegetables, fruits, and herbs. This book discusses the nature and role of these compounds by studying the molecular mechanism of flavonoids using spectroscopy and computational tools. The book also addresses the characteristics of natural vs. synthetic colors from both chemical and biological points of view. More importantly, a lengthy chapter explains in full detail the usefulness of these natural coloring properties to provide a safe, efficient, and economic therapy and/or prophylaxis of many health problems, e.g. obesity and cardiovascular disorders. This book poses a balance between developments in scientific research and the idea that researchers must be able to absorb and link scientific advances with clinical practice so that the management of diseases can be based on sound physiological concepts.